N-acetylcysteine, xCT and suppression of Maxi-chloride channel activity in human placenta. (July 2021) - Lofthouse, Emma M.; Manousopoulou, Antigoni; Cleal, Jane K.; O'Kelly, Ita M.; Poore, Kirsten R.; Garbis, Spiros D.; Lewis, Rohan M.
Abstract: Introduction: Placental oxidative stress features in pregnancy pathologies but in clinical trials antioxidant supplementation has not improved outcomes. N-acetylcysteine (NAC) stimulates glutathione production and is proposed as a therapeutic agent in pregnancy. However, key elements of N-acetylcysteine biology, including its cellular uptake mechanism, remains unclear. This study explores how the cystine/glutamate transporter xCT may mediate N-acetylcysteine uptake and how N-acetylcysteine alters placental redox status. Methods: The involvement of xCT in NAC uptake by the human placenta was studied in perfused placenta and Xenopus oocytes. The effect of short-term N-acetylcysteine exposure on the placental villous proteome was determined using LC-MS. The effect of N-acetylcysteine on Maxi-chloride channel activity was investigated in perfused placenta, villous fragments and cell culture. Results: Maternoplacental N-acetylcysteine administration stimulated intracellular glutamate efflux suggesting a role of the exchange transporter xCT, which was localised to the microvillous membrane of the placental syncytiotrophoblast. Placental exposure to a bolus of N-acetylcysteine inhibited subsequent activation of the redox sensitive Maxi-chloride channel independently of glutathione synthesis. Stable isotope quantitative proteomics of placental villi treated with N-acetylcysteine demonstrated changes in pathways associated with oxidative stress, apoptosis and the acute phase response. Discussion: This study suggests that xCT mediates N-acetylcysteine uptake into the placenta and that N-acetylcysteine treatment of placental tissue alters the placental proteome while regulating the redox sensitive Maxi-chloride channel. Interestingly N-acetylcysteine had antioxidant effects independent of the glutathione pathway. Effective placental antioxidant therapy in pregnancy may require maintaining the balance between normalising redox status without inhibiting physiological redox signalling. Graphical abstract: Image 1 Highlights: - xCT is expressed on the MVM of the placental syncytiotrophoblast - xCT mediates glutathione precursor uptake into placenta from maternal circulation - N-acetylcysteine decreases activity of the redox sensitive Maxi-chloride channel - N-acetylcysteine affects proteins in redox sensitive signalling pathways - N-acetylcysteine supplementation in pregnancy may modulate placental redox status